AI-driven Protein Engineering for DNA Sequence Modification - Lin, Luqi; Cui, Zhengrong; Wang, Sihao; Chen, Yizhi; Zong, Yanqi (Journal of Theory and Practice of Engineering Science, 2024)
The integration of artificial intelligence (AI) with gene editing technologies like CRISPR-Cas9 holds immense promise for advancing biomedical research and personalized medicine. This article highlights the crucial role of AI in predicting and minimizing off-target effects, thereby enhancing the precision and efficiency of gene editing. Researchers have developed algorithms like BE-DICT to accurately predict base editing outcomes, showcasing the potential of AI-driven strategies in optimizing gene editing processes. By combining AI with bioengineering, this interdisciplinary approach aims to automate and refine DNA modifications, paving the way for innovative applications in personalized gene therapy and biofabrication. Ultimately, this research endeavors to revolutionize the life sciences field, leading to significant breakthroughs in healthcare and biotechnology.